(untitled) (Indian Journal of Public Health Research & Development, 2020)
Medical service conditions in government hospitals in South Sulawesi show a lack of meaningful change in alertness and responsiveness from hospital staff in servicing their patients. This study found that the volume of patient complaints was quite high, despite improvements in service procedures involving improvements in service standards and changes in counter-based service mechanisms. This case study focuses on in-depth analysis of the ethical responsiveness of service providers at patient registration desks and medical action counters. Data was collected via accidental sampling on both inpatient and outpatient services from the months of May to Augusts of 2016. Interactive data analysis was performed throughout data collection to conclusion. Results showed that overall service in the Wahidin Sudirohusodo Makassar Regional Hospital was poor with inconsistent implementation of ethical responsiveness in comparison to the Regional Hospital of the Regency of Barru. Impressions of the registration process, where initial interactions between patients and counter clerks first occurred, were overwhelmingly negative. This was the case in both the Makassar hospital and the Barru hospital, with feedback generally more positive at the Barru location. Geographical factors and the volume of patients serviced by medical and non-medical staff were the primary determining factors underlying ethical responsiveness in service quality.